2021
DOI: 10.3389/fvets.2021.611931
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Integration of One Health in Surveillance Systems for Antimicrobial Use and Resistance: A Conceptual Framework

Abstract: It is now widely acknowledged that surveillance of antimicrobial resistance (AMR) must adopt a “One Health” (OH) approach to successfully address the significant threats this global public health issue poses to humans, animals, and the environment. While many protocols exist for the evaluation of surveillance, the specific aspect of the integration of a OH approach into surveillance systems for AMR and antimicrobial Use (AMU), suffers from a lack of common and accepted guidelines and metrics for its monitoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 33 publications
0
55
0
Order By: Relevance
“…Publications from the international CoEval-AMR Network ( 27 ), released in March 2021, parallel the processes we undertook to test and refine evaluation frameworks and tools for AMR/AMU surveillance. Aenishaenslin et al, for example, reported on their development of the ISSE framework and piloted the tool to review one Canadian AMR surveillance program, CIPARS, a sentinel surveillance program for animal and human health ( 22 ). The authors began their process with CIPARS program experts to determine an evaluation framework and then conducted the program evaluation in a stepwise fashion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Publications from the international CoEval-AMR Network ( 27 ), released in March 2021, parallel the processes we undertook to test and refine evaluation frameworks and tools for AMR/AMU surveillance. Aenishaenslin et al, for example, reported on their development of the ISSE framework and piloted the tool to review one Canadian AMR surveillance program, CIPARS, a sentinel surveillance program for animal and human health ( 22 ). The authors began their process with CIPARS program experts to determine an evaluation framework and then conducted the program evaluation in a stepwise fashion.…”
Section: Discussionmentioning
confidence: 99%
“…At the time of this analysis (2019), we did not find any tools that met our specific needs for comprehensive evaluation of all integrated, One Health elements of an AMR/AMU surveillance program. In March 2021, Aenishaenslin et al published a new Integrated Surveillance System Evaluation (ISSE) framework, which is a conceptual framework for evaluating the integration of One Health surveillance systems for AMR and AMU ( 22 ). Very useful for future evaluations, it presented a framework for developing an evaluation protocol but did not provide an explicit tool in itself, thus would not have suited our immediate purpose.…”
Section: Methodsmentioning
confidence: 99%
“…For each level, a set of evaluation questions are defined, and links are made with existing evaluation tools. A semi-quantitative scale is applied to show the level of integration of the surveillance system ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…Existing tools for evaluation of surveillance [e.g., ( 12 , 13 )] are not necessarily appropriate for integrated surveillance as they might not address aspects such as collaboration across sectors ( 12 , 14 ). Characteristics of OH surveillance programs have been described, and recently, tools to evaluate integrated surveillance systems have emerged, targeting different aspects of the OH or other integrated surveillance activities ( 7 , 11 , 15 19 ). A tool may have been made for evaluation of a particular type of surveillance system, such as animal health surveillance.…”
Section: Introductionmentioning
confidence: 99%
“…E. coli strains showing multidrug resistance and producing blaNDM-5 plasmid were identified in human, animal, and food isolates, and plasmids in these strains were sequenced using the whole genome sequencing style (He et al 2017, Feng et al 2018, Xie et al 2018, Tyson et al 2019, Marchetti et al 2020. It is important to determine the survelliance of the resistance profiles of the strains obtained from different disciplines in a one health approach (Aenishaenslin et al 2021). In our study, we aimed to examine the in silico analysis of resistance gene identifiers with human and animal blaNDM-5 plasmids in the open database and to compare these resistance genes.…”
Section: Introductionmentioning
confidence: 99%